If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -2x + 3y = 0 Solving 1 + -2x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -2x + -1 + 3y = 0 + -1 Reorder the terms: 1 + -1 + -2x + 3y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x + 3y = 0 + -1 -2x + 3y = 0 + -1 Combine like terms: 0 + -1 = -1 -2x + 3y = -1 Add '-3y' to each side of the equation. -2x + 3y + -3y = -1 + -3y Combine like terms: 3y + -3y = 0 -2x + 0 = -1 + -3y -2x = -1 + -3y Divide each side by '-2'. x = 0.5 + 1.5y Simplifying x = 0.5 + 1.5y
| (7x-y)(6x-y)(-x-y)+21x^3=0 | | 4x^2-15x+11=-7x+8 | | -x-4=5x+2 | | 63=-28y | | a-2b+7b-a= | | 4x=6y | | 3x-15=55 | | 5x+29=13x-57 | | 4[y+3]=6 | | 6+8r-2=6+5r-5 | | 2(68)+5=3(68)+8 | | 7a+3k+4a+6k+a= | | 6x^2+7x-11=0 | | 28x^2-14x=0 | | -8b=-24 | | (a+5)(a^2-8a+8)= | | 1620=0.09/8 | | .66n=-.75 | | 10r^2-43r+28=0 | | -10n+3(8n)=-6(n-4) | | .66n-1=.25 | | -3x-5=5x-21 | | 6x=-16x+7 | | 2x+4.7=6.9 | | 9x-16=-97 | | 4x+30=3+8x-5 | | 2x^2+12x=3x+18 | | 6x-11=29 | | 5-.5(4x+6)=-3x-8 | | 5(2r+7)=70 | | -8(x-4)-10x= | | -1.4=2.6-2y |